Linking personal initiative and family help as well as social support: a case study of learning challenges and solutions for older adults in rural China during the COVID-19 pandemic - Cheng, Hao (Frontiers in Public Health, 2024)
The sudden outbreak of the COVID-19 Pandemic has caused serious damage to the continuous learning of older adults around the world. While the existing literature focused more on older adults' learning in developed countries, few studies explored older adults' learning in developing countries with low social and cultural capital. Methods: This study took family-school cooperation in China as the platform and explored learning challenges and solutions through unstructured interviews with 12 older adults.The study found that due to policies of working and studying from home, older adults face obstacles in accessing physical learning institutions and digital learning knowledge, skills, and psychology. I further found that the older adults were not forced to accept the challenge passively, but created a lifelong learning model with Chinese characteristics by building self-learning based on personal initiative, developing sustainable intergenerational learning rooted in Chinese family culture, and participating in online learning in schools and enterprises under the government guidance.This study provided new knowledge for understanding the learning challenges and solutions of older adults in rural China. It is emphasized that policy value and practice enlightenment were highlighted and discussed in conversations with active aging, intergenerational learning, and harmonious societies.